PKM PENYULUHAN YUK, BERMAIN DENGAN MATEMATIKA DI SDN CIBITUNG KULON 01 PAGI - Dyah Anungrat Herzamzam; Risky Dwiprabowo (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2020)
The teacher acts as a learning center so that students are less actively involved during learning. This condition makes mathematics learning less attractive to students and as a result students are less enthusiastic during the learning process. Designing a learning process through a lesson plan (RPP) in the classroom is important. Sometimes this RPP is limited to administrative fulfillment only. Learning with good lesson plan preparation, makes the learning process in the classroom organized and directed and easy to evaluate for the next process. The instrument in this community service activity is the observation sheet while the data collection technique through observation is used to observe all participant activities during the socialization activity. The data that has been obtained will then be processed and presented in descriptive form. The implementation of this program is aimed at teachers of SDN Cibitung Kulon 01 Pagi. Based on the evaluation in the implementation of this socialization and counseling program, it was found that the participants who attended this program had already met the target, namely 39 participants who came from 43 targeted participants. The conclusion obtained is that this socialization activity can increase the knowledge of teachers about how to create fun mathematics learning in class. Furthermore, the implementation of this community service activity program has run smoothly and as expected, both by members of the extension team and participants of the community service program.